Synthesis and Application of Diaryl Ether-Derived Monodentate Phosphine Ligands for the Pd-Catalyzed Arylation of Amines - Ma, Qicai; Wang, Wenjing; Fu, Cong; Li, Shanyue; Zhou, Wei (Synlett, 2025)
A set of diaryl ether-derived monodentate phosphine ligands (DAE-Phos) are reported, which can be easily synthesized from readily available starting materials. In contrast to the dialkyl-ortho-biaryl class of phosphines, commonly known as Buchwald-type ligands, DAE-Phos bears a more flexible diaryl ether side chain. With the Pd/L7 catalyst, a wide range of (hetero)aryl chloride coupled well with amines under 1 mol% catalyst loading and solvent-free condition.
Keywords: Diaryl ether; Phosphine ligand; Pd-catalyzed; C–N coupling; Amine